The Impact of Religious Spiritual Care Training on the Ability and Spiritual Health of the Family Caregivers of Older Adults during the COVID-19 Pandemic: A Field Trial - Afifeh Qorbani; Shahnaz Pouladi; Akram Farhadi; Razieh Bagherzadeh; Mohtaram Shekariyan (Iranian South Medical Journal)
Background: During times of crisis, the family caregivers of older adults need heightened attention to their own health. This study aimed to examine the impact of religious spiritual care training on the ability and spiritual health of family caregivers of older adults in Bushehr, Iran, during the COVID-19 pandemic. Materials and Methods: A field trial was conducted on 80 family caregivers of older adults referring to comprehensive health centers and the Comprehensive Rehabilitation Center in Bushehr by random sampling in 2022. Pouladi’s ability questionnaire and Polotzin's and Ellison's Spiritual Health Questionnaire were administered. The experimental group received spiritual religious training. Data were analyzed in SPSS version 19. Results: The mean change in the total ability scores was -0.87 ± 8.44 in the experimental group, while the control group exhibited a mean change of 0.27 ± 0.87. The mean change in the total spiritual health scores was 5.05 ± 11.12 in the experimental and -0.47 ± 0.96 in the control groups. Religious spiritual care training was effective in improving the physical-psychological ability of the research population (p=0.045), but it was not effective on the other areas of ability and overall ability (p>0.05). Religious spiritual intervention was effective in improving the existential dimension of spiritual health (p=0.001) and overall spiritual health (p=0.002), but it was not effective on the religious dimension of spiritual health (p>0.05) Conclusion: The effect of spiritual religious care training on physical-psychological ability and the existential dimension of spiritual health in the caregivers indicates the usefulness of the religious spiritual care model for strengthening the caregivers' physical, psychological, and care behavior. Further studies are recommended to explore the factors contributing to the other domains of ability and the religious dimension of spiritual health and to enhance caregivers' empowerment and spiritual health.